Use of natural and anthropogenic land cover by wintering Yellow Warblers: The influence of sex and breeding origin. (2nd May 2018) - Valdez-Juárez, Simón O.; Drake, Anna; Kardynal, Kevin J.; Hobson, Keith A.; Krebs, Elizabeth A.; Green, David J.
Abstract: Sex, age, body size, and breeding origin can influence the nonbreeding distribution of long-distance migratory birds. At continental scales, differential migration can lead to segregation of various classes or populations among different regions. At local scales, class segregation can occur among habitats of differing qualities, often due to dominance interactions related to sex, age, and body size. Conversion of natural habitats to agriculture in the Neotropics is leading to more birds wintering in modified landscapes. We examined how sex, age, size, and breeding origin influenced the use of 3 land cover types (riparian gallery forest, coastal lagoon vegetation, and agriculture) by wintering migratory Yellow Warblers ( Setophaga petechia ) in western Mexico. Between 2012 and 2014, we used point counts in 6 study sites to estimate Yellow Warbler densities, and we captured, sexed, and aged 205 birds to characterize individuals using each land cover type. Breeding origin was inferred using stable hydrogen isotope ratios (δ 2 H) in feathers. Contrary to our expectations, Yellow Warbler densities were highest in agricultural sites (5.6 ± 0.7 SE birds ha −1 ) and lower in sites with natural land cover (riparian gallery forest: 3.6 ± 0.5 birds ha −1 ; scrub mangrove: 2.0 ± 0.4 birds ha −1 ). The Yellow Warbler population wintering in our study sites was male-biased (64%), and the use of sites with natural vs. agricultural land cover was not influenced by sex, age, or size of individuals, suggesting that competitive interactions are not limiting access to sites with different land cover. We found that females from more northerly breeding or natal origins were more likely to winter in sites with natural land cover, while females from more southerly origins were more likely to use agricultural sites. Our results suggest that localized population declines could occur via survival differences or carryover effects if condition or subsequent reproductive success differs between birds wintering in sites with natural vs. agricultural land cover.